AI-Driven Customer Segmentation and Targeting in Retail Banking: Improving Marketing Strategies and Customer Retention - Mohit Kumar Sahu (Journal of Science & Technology, 2022)
In the contemporary landscape of retail banking, the advent of Artificial Intelligence (AI) has ushered in transformative advancements in customer segmentation and targeting, which are pivotal to optimizing marketing strategies and enhancing customer retention. This paper delves into the application of AI technologies in refining customer segmentation processes and crafting targeted marketing strategies, underpinned by data-driven insights. The integration of AI in these domains is analyzed through various methodological frameworks and practical implementations, highlighting its efficacy in dissecting complex customer datasets to generate actionable insights. AI-driven customer segmentation leverages machine learning algorithms and advanced analytics to process and interpret vast quantities of customer data, facilitating a granular understanding of customer behaviors, preferences, and demographic characteristics. Traditional segmentation approaches, often limited by their reliance on static criteria and historical data, are significantly outperformed by AI methodologies which utilize dynamic, real-time data inputs. This dynamic capability allows for the development of more nuanced customer profiles, which in turn supports the creation of highly tailored marketing strategies. The paper explores various AI techniques, including supervised and unsupervised learning models, clustering algorithms, and natural language processing (NLP), that are employed to dissect customer data. Supervised learning models, such as decision trees and neural networks, are particularly effective in predicting customer behaviors and preferences based on historical data. Unsupervised learning models, including k-means clustering and hierarchical clustering, are utilized to uncover hidden patterns and groupings within customer datasets. Furthermore, NLP techniques are instrumental in analyzing customer interactions and feedback, providing additional layers of insight into customer sentiment and preferences. Case studies of retail banking institutions that have successfully implemented AI-driven segmentation strategies illustrate the practical benefits of these technologies. These case studies highlight significant improvements in marketing effectiveness, evidenced by increased response rates to targeted campaigns and enhanced customer engagement. Additionally, the paper discusses the impact of AI on customer retention, emphasizing how predictive analytics can identify at-risk customers and inform retention strategies tailored to individual needs. The challenges associated with implementing AI-driven customer segmentation are also examined. Issues such as data privacy, algorithmic bias, and the integration of AI systems with legacy banking infrastructure are discussed in detail. Addressing these challenges is crucial for ensuring the ethical and effective application of AI technologies in retail banking. The paper concludes with a discussion on future trends in AI-driven customer segmentation and targeting, including the potential for integrating emerging technologies such as blockchain for enhanced data security and the evolving role of AI in personalizing banking experiences. As the banking sector continues to evolve, the role of AI in shaping marketing strategies and improving customer retention is expected to become increasingly significant.